Relationship between student teachers’ achievement in professional education courses and their achievement in teaching practices - Othman, Ikhsan; Md Salleh, Norila (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2016)
Professional Education Course (PEC) and Teaching Practice (TP) are two main components in teacher education program. This paper discusses findings of a study to identify the relationship between students’ achievement in PEC and their achievement in TP. Grades achieved by the students in PEC and their grades achieved in TP were used and analyzed with permission from the Academic Department of a selected university. The data of 1,888 students were from 28 programs conducted at the university. Spearman’s rho correlation via SPSS version 23 was used for data analysis. There were five sub courses under PEC that were analyzed in this study. The analysis found that, only students’ achievement in three courses of PEC showed significant correlation with their achievement in TP with correlation indexes in a range of .046 < r < .088 at p ≤ .05. It showed that there was a weak significant correlation between students’ achievement in PEC and the students’ achievement in TP. Students’ achievement in the remaining two courses of PEC had no significant correlation with their achievement in TP. Therefore, it can be said that students’ achievement in PEC cannot be used as predictor to the students’ achievement in TP. However, from random interviews of the students, PEC was said to have positive contribution to them in performing their TP. Further equivalent studies are needed to be conducted in order to get idea on the consistency of the relationship between students’ achievement in PEC and their achievement in TP.